Employment of molecular dynamics simulations in the investigation of biological systems. - Yip, Yew Mun. (2013)
Diseases and viruses are prevalent in the world today. While many of the disease pathways have been unearthed, many are still trying to locate the key proteins that have the greatest impact on inhibiting the disease. Upon discovering these proteins, potential inhibitors would then be synthesized and tested in vitro before they